Prediction of hyperelastic material sealing pressure using experimental and numerical analyses. (December 2020) - Sukumar, T; Ramesh Bapu, BR; Durga Prasad, B
In commercial vehicle air braking system, leakage is one of the major problems and will affect the performance of the vehicle braking in terms of brake pedal travel and stopping distance. If there is any leakage in the brake system, the vehicle stopping distance will not meet the safety regulations. One of the main reasons for braking system leakage is ineffective sealing mechanism. The majority of sealing elements used in the air brake system are O-rings, lip seals, and gaskets. This article presents an experimental procedure for measuring the sealing pressure between an O-Ring and its mating parts. The contact pressure measurement was performed in a static condition by means of an experimental test rig using Fuji film. For the sealing pressure study, a test rig was properly designed to replicate the actual operating conditions. Contact pressure was evaluated by means of Fuji film interposed between the O-ring and its mating parts. The sealing pressure tests were carried out for different clamping load conditions. The experimental results were compared with the numerical result using the finite-element analysis (FEA). A good correlation was found between the experimental and the numerical results. The outcome from the experimental results will be useful for finalizing the hyperelastic material models, which are input to the FEA for future reference.